Cost-utility of a web-based intervention to promote maternal mental health among postpartum women presenting low risk for postpartum depression. (21st July 2022) - Monteiro, Fabiana; Antunes, Patrícia; Pereira, Marco; Canavarro, Maria C.; Fonseca, Ana
Abstract: Objectives: Web-based interventions for the promotion of maternal mental health could represent a cost-effective strategy to reduce the burden associated with perinatal mental illness. This study aimed to evaluate the cost-utility of Be a Mom, a self-guided web-based cognitive behavioral therapy intervention, compared with a waiting-list control. Methods: The economic evaluation alongside a randomized controlled trial was conducted from a societal perspective over a 14-month time frame. Postpartum women presenting low risk for postpartum depression were randomized to the intervention ( n = 191) or control ( n = 176) group and assessed at baseline, postintervention and 4 and 12 months after postintervention. Data regarding healthcare use, productive losses and quality-adjusted life years (QALYs) were collected and used to calculate incremental cost-effectiveness ratios (ICERs). Uncertainty was accounted for with nonparametric bootstrapping and sensitivity analyses. Results: At 14 months, and after accounting for a 3.5 percent discount rate, the intervention resulted in a yearly cost-saving of EUR 165.47 (−361.77, 28.51) and a QALY gain of 0.0064 (−0.0116, 0.0244). Bootstrapping results revealed a dominant ICER for the intervention group. Although results were statistically nonsignificant, cost-effectiveness acceptability curves showed that at a EUR 0 willingness to pay threshold, there is a 96 percent probability that the intervention is cost-effective when compared with the control group. The sensitivity analyses generally supported the acceptable likelihood of the intervention being more cost-effective than the control group. Conclusions: From a societal perspective, the implementation of Be a Mom among low-risk postpartum women could be a cost-effective way to improve perinatal mental health.